Synthesis of 3-Amino-1,5-benzodiazepine-2-one Derivatives from Dehydroalanine Derivatives - Obara, Nobuhiro; Watanabe, Takeshi; Asakawa, Tomohiro; Kan, Toshiyuki; Tanaka, Takao (Synthesis, 2019)
A convenient method was developed for synthesizing 3-amino-1,5-benzodiazepine-2-one derivatives via a Michael addition reaction of o-phenylenediamine with dehydroalanine HFI or HOBt ester derivatives (HFI = 1,1,1,3,3,3-hexafluoro-2-propyl; HOBt = 1,2,3-benzotriazol-1-ol monohydrate), followed by cyclization. Interestingly, the regio- and diastereoselectivities were confirmed by comparing the HFI and HOBt esters. These simple methods were used to synthesize various N-substituted 3-amino-1,5-benzodiazepine-2-one derivatives in good yields.
Keywords: 1,5-benzodiazepines; Michael additions; o-phenylenediamine; dehydroalanine; intramolecular cyclization